2022
DOI: 10.3390/ijms23116198
|View full text |Cite
|
Sign up to set email alerts
|

No Time to Die: How Kidney Cancer Evades Cell Death

Abstract: The understanding of the pathogenesis of renal cell carcinoma led to the development of targeted therapies, which dramatically changed the overall survival rate. Nonetheless, despite innovative lines of therapy accessible to patients, the prognosis remains severe in most cases. Kidney cancer rarely shows mutations in the genes coding for proteins involved in programmed cell death, including p53. In this paper, we show that the molecular machinery responsible for different forms of cell death, such as apoptosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 182 publications
0
12
0
Order By: Relevance
“…When the concentration of ROS exceeds the elimination capacity of the antioxidant system, ROS can oxidize unsaturated fatty acids in the cell membrane to form lipid peroxides, which can damage the structure and function of cells directly or indirectly ( Xie & Guo, 2021 ). In recent years, the deregulation of ferroptosis was associated with numerous human pathologies, including cancer ( Ganini et al, 2022 ). Ferroptosis can promote tumorigenesis and cancer progression by inducing gene mutations and epithelial–mesenchymal transition and implicating other mechanisms ( Tang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When the concentration of ROS exceeds the elimination capacity of the antioxidant system, ROS can oxidize unsaturated fatty acids in the cell membrane to form lipid peroxides, which can damage the structure and function of cells directly or indirectly ( Xie & Guo, 2021 ). In recent years, the deregulation of ferroptosis was associated with numerous human pathologies, including cancer ( Ganini et al, 2022 ). Ferroptosis can promote tumorigenesis and cancer progression by inducing gene mutations and epithelial–mesenchymal transition and implicating other mechanisms ( Tang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ferroptosis can promote tumorigenesis and cancer progression by inducing gene mutations and epithelial–mesenchymal transition and implicating other mechanisms ( Tang et al, 2021 ). It is reported that kidney cancer shows high susceptibility to ferroptosis ( Ganini et al, 2022 ; Chen et al, 2022c ). As a result, ferroptosis-related biomarkers may be useful as both diagnostic and therapeutic targets for ccRCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regulated cell death programmes probably evolved to protect complex organisms 32 , and these protective roles should be considered when developing approaches to target cell death therapeutically. Kidney cancer cells have developed mechanisms to evade cell death 33 , whereas inactivating genetic variants of the genes involved in cell death processes have long been known to contribute to the impaired deletion of self-reactive immune cells and the development of autoimmunity 34 , 35 . However, untimely, unwanted or excessive cell death can deplete important parenchymal cells and cause tissue injury.…”
Section: Targeting Cell Death In Kidney Diseasementioning
confidence: 99%
“…Ideally, such unwanted cells should be cleared by promoting apoptosis, given the potential adverse pro-inflammatory consequences of regulated necrosis that might amplify kidney injury by invoking a more intense inflammatory response or by triggering autoimmunity. Kidney cancer may be an exception, since promoting regulated necrosis-induced immunogenicity towards malignant cells may be beneficial 33 . In other contexts, the need to both promote and prevent cell death should be balanced.…”
Section: Targeting Cell Death In Kidney Diseasementioning
confidence: 99%